Wellness for a healthy Asia. - Park, Donghyun; Quising, Pilipinas; GerardHelble; MatthiasQureshi; IrfanTian, Shu; Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
Wellness, or the active pursuit of holistic health, can contribute to sustainable development.The book takes stock of wellness in the region, including the growing wellness economy. It discusses policies in four crosscutting areas: creating a healthy built environment, supporting physical activity, encouraging healthy diets, and enhancing wellness in the workplace. It notes the importance of a lifelong wellness policy framework and of investments in infrastructure such as community recreation centers and green parks in poor neighborhoods, as well as health education campaigns.
COVID-19 Brings Wellness to the Fore - - Contours of Wellness in Asia - - Holistic Pathways to Physical Wellness - - Leveraging Asian Traditions for Mental Wellness - - Wellness for Happiness and Inclusion - - Appendixes.
Keywords: Primary health care -- Developing countries; Hygiene; Industry regulation; Electronic book